Personnel factors of corporate internal auditing on the contemporary microeconomics environment in the United States - Victor W Gaines; Karina Kasztelnik (Contemporary Economics, 2021)
The purpose of this quantitative, correlational research was to examine to what extent the personnel factors of internal auditing departments predict the control environment within the public sector. Using the 2013 COSO Internal Control-Integrated Framework as the theoretical framework, we addressed the extent to which the internal audit staffing size per engagement, professional development, and auditing experience of auditors predict the overall control environment and each of the five components of COSO. The results of six multiple linear regression models showed no statistically significant with the exception between professional development and Principle 4 - Recruitment. A nonparametric Kendall's tau-b correlation analysis revealed a significant relationship between professional development and Principle 4 Recruitment, τb = 0.388, p = 0.030. The results of this study may contribute to the positive global economy change by bringing into focus the role of auditing and its positive impact on the worldwide public auditing policy.
Keywords: H83; M42; M48; 330; COSO; Government Auditing; Governance; Internal Auditing; Personnel Factors; Control Environment